Analysis Of Increasing Types Of Online Fraud And Level Of Public Awareness In Indonesia - Hans Marwi; Inong Oskar (Journal of Embedded Systems, Security and Intelligent Systems, 2023)
Technological developments have various impacts on society, both positive and negative. With the increasingly rapid growth of e-commerce and the variety of applications and sites available, the number of online transactions is also increasing. But on the other hand, the level of crime that occurs on the Internet is also increasing. Online fraud is increasingly occurring with various types and media used. This research aims to find ways to improve security so that public interest in online transactions can increase. Apart from efforts by business people and legal and government officials, the level of public awareness also needs to be increased. The research method was carried out using literature methods, observation and direct involvement with the activities of online fraudsters, surveys of respondents from various demographics, conducting interviews and simulating fraud on several respondents. The research results show varying levels of awareness, but there are still those who are deceived. The researcher proposes several solutions at the end of the article.